Clinical Value of Serum Ca 19.9 Level as a Tumor Marker in Pancreatic Malignancy - Jahan, SM Sarwar; Hussain, Md Margub; Islam, Md Tawhidul; Dewan, Md Nayeem; Das, Prosunto Kumar; Alam, Shoaeb Imtiaz (Journal of Dhaka Medical College, 2025)
Background: Pancreatic cancer carries a poor prognosis; at operation approximately 25% of patients are found to have unresectable tumours even though CT has demonstrated that they are resectable. At our tertiary care centre, we intended to find out if there is an optimum cut-off value for the CA 19-9 level preoperatively that will indicate that the pancreatic cancer is unresectable despite radiologic imaging that suggests otherwise according to receiver operating characteristic (ROC) curve analysis. Objective: To evaluate the clinical value of serum CA19-9 levels in predicting the resectability of pancreatic carcinoma according to receiver operating characteristic (ROC) curve analysis. Materials & Methods: This study prospectively analyzed the clinical and imaging data including preoperative CA19-9 level in 25 patients with pancreatic cancer who underwent surgical resection in the department of surgery, DMCH from February 2012 to January 2013. Resectability of pancreatic cancer was evaluated at least by preoperative bolus-contrast, triple-phase helical computer tomography (CT) scan. ROC curve was plotted for the CA19-9 levels. The point closest to the upper left-hand corner of the graph were chosen as the cut-off point. The sensitivity, specificity values of CA19- 9 at this cut-off point were calculated. Results: Resectable pancreatic cancer was detected in 09 (36%) patients and unresectable pancreatic cancer was detected in 16 (64%) patients. The cut-off point of CA19-9 level was calculated to be 188 U/mL and the sensitivity and specificity of CA19-9 at this cut-off point were 86.67% and 80.00% respectively. Conclusion: Preoperative serum CA19-9 level is a useful marker for further evaluating the resectability of pancreatic cancer. Thus increased serum levels of CA19-9 (> 188 U/mL) can be regarded as an ancillary parameter for unresectable pancreatic cancer. J Dhaka Med Coll. 2024; 33(1) : 3-6